RESPON MASYARAKAT TERHADAP PROGRAM JAMINAN KESEHATAN MASYARAKAT DI PUSKESMAS MANDALA KECAMATAN MEDAN TEMBUNG KOTA MEDAN - FORMAN N TAMBUNAN (Welfare StatE, 2013)
Publict Response From Health Insurance Programs in Mandala’s Health Center District of   Medan Tembung Medan City Health is closely related to economic conditions. Economic established by itself will create good health. With economic conditions properly it will affect the health condition. But on the contrary, a bad economy will make it difficult for individual communities improve their health each. Bad economy will lead to the difficulty of the individual to gain access to adequate health because expensive health costs. This resulted in poor people struggling in the same condition. Poverty and disease are related to each other, with the direction of relationships never end unless intervention on one or both sides of any person entitled to receive health care because health is the most important element in human life. To guarantee the right to health of the community, the government, through the Ministry of Health issued a guarantee program for basic human needs as an obligation of the state. Program called the Community Health aims to ensure the health care needs of individuals who deserve it. This is a descriptive study with the population are 7252 and sample totaled 15 people. Sampling conducted by purposive sampling, the sampling intentionally done by selecting the respondent in such a way. Sample or the respondents in this study were participants in Mandala’s Health Center  Jamkesmas program, and the results of these studies are tabulated into frequency tables further analyzed, and used a Likert scale to measure the variables. Based on the data that has been collected and analyzed can be summarized in average proggram Jamkesmas received a positive response from the participants with a value of 0.76. Consisting of perceptions and attitudes to the value of 0.80 to 0.87 and the value of participation with the value 60. Participants hope Jamkesmas program continued and further enhanced in the ministry. Keywords: Community Response, Health Insurance